Peran Sosialisasi Peningkatan Praktek Hidup Bersih dan Sehat (PHBS) dalam Meningkatkan Kesehatan Siswa di SD Al Maksum Desa Balunganyar Kecamatan Lekok - Aulia Ainindia Wanti; Siti Ma’rifatul Mahbubah; Laila Fitriyatus Sholihah; Eli Masnawati; Mila Hariani; Rahayu Mardikaningsih; Fayola Issalillah; Rafadi Khan Khayru; Arif Rachman Putra; Adi Herisasono (Jurnal Kabar Masyarakat, 2025)
Health problems among students at Al Maksum Elementary School, Balunganyar Village, Lekok District, are still a concern due to a lack of knowledge and awareness of Clean and Healthy Living Practices (PHBS). This condition increases the risk of diseases that interfere with children's learning and growth and development. This research aims to improve student health through the socialization and implementation of PHBS using the Participatory Action Research (PAR) method, which involves students, teachers and health workers in planning, implementation and evaluation. Socialization includes education about personal hygiene, hand washing, cleanliness of the school environment, and the importance of healthy food. Direct practice is also carried out to strengthen the implementation of PHBS. As a result, there has been an increase in students' understanding and changes in behavior, with higher awareness of personal and environmental hygiene, as well as discipline in implementing PHBS. As a result, student health improves, health complaints decrease, and attendance increases. It is hoped that this activity will be carried out in a sustainable manner by involving parents and the community to create a supporting environment and maintain the sustainability of PHBS implementation.